Performance evaluation of concatenated coding with diversity reception for body area network - Sansoda, Buncha; Choomchuay, Somsak (My University, 2016)
In wireless communication, it is of significance that the receiving information should be identical to the transmitted information. With this regards, an application of error correction coding (ECC) is one suitable method for maintaining the information precision between the transmission channels. With similar objectives, the diversity techniques are used to moderate the devaluation in the error performance due to the fading impairment by using multiple communication branches. This paper, we propose the application of concatenate codes combined with space diversity technique as maximal ratio combining. We focused on the bit error rate (BER) performance and the impact of Rician fading channel on wireless body area network (WBAN). The finding shows that the proposed scheme can provide considerable improvement on the BER performance compared with that of the traditional system. The concatenate code with MRC outperformed conventional ones, either RS or convolutional codes. At 10-4 of BER, the designed scheme is better than RS code by1.3 dB and convolutional code by2.2dB.
Keywords: concatenate code; ECC; MRC; WBAN